2018
DOI: 10.1080/1612197x.2018.1462230
|View full text |Cite
|
Sign up to set email alerts
|

Consultant characteristics in sport psychology service provision: A critical review and future research directions

Abstract: The sport psychology consultant's (SPC) first impression and rapport building with potential clients is vital to 'gaining entry' -the precursor to subsequent service provision.Understanding those characteristics of the consultant that influence the clients' preference and likelihood to seek psychological services contributes to the development of educational training programs for neophyte practitioners, and marketing tools for the field as a whole.This article offers a critical review of studies that have inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…Additionally, in a qualitative study with eight NCAA D1 coaches, one male coach of female athletes expressed an interest in a female practitioner as this coach recognized that some issues might not be comfortable to talk about with an all-male coaching staff (Zakrajsek et al, 2013). More recently, Woolway and Harwood (2020) found in their literature review that the most preferred sport psychology practitioner was that of the same gender. Taken together, the gender of the practitioner appears to be a characteristic worthy of inclusion, but has yet to be when examining the state of sport psychology services in NCAA athletic departments.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…Additionally, in a qualitative study with eight NCAA D1 coaches, one male coach of female athletes expressed an interest in a female practitioner as this coach recognized that some issues might not be comfortable to talk about with an all-male coaching staff (Zakrajsek et al, 2013). More recently, Woolway and Harwood (2020) found in their literature review that the most preferred sport psychology practitioner was that of the same gender. Taken together, the gender of the practitioner appears to be a characteristic worthy of inclusion, but has yet to be when examining the state of sport psychology services in NCAA athletic departments.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…Hings et al (2018Hings et al ( , 2020 for example suggested there is a level of emotional labour that SSMPs take on in a role; donning a "professional mask" they are required to demonstrate emotional control and manage themselves during interactions in order to build trust, rapport and ultimately relationships and engagement. Whilst Woolway and Harwood (2018) suggested the importance of developing interpersonal qualities, alongside an understanding of how to interact with clients and the positive and negative effects their interactions could have.…”
Section: Importance Of the Interpersonalmentioning
confidence: 99%
“…I now derive confidence, pride and self-respect from a task-oriented approach (see Nicholls, 1984). The characteristic ranked as one of the most important for sport psychology practitioners is high interpersonal skills; this potentially encompasses qualities such as being likeable, approachable, trustworthy, and empathic (Tod, Hutter, & Eubank, 2017;Woolway & Harwood, 2018). These qualities are critical to building rapport.…”
Section: Reflectionsmentioning
confidence: 99%